Identifying Undamaged-Beam Status Based On Singular Spectrum Analysis And Wavelet Neural Networks / Sy Dzung Nguyen, Quoc Hung Nguyen, Kieu Nhi Ngo - Sy Dzung Nguyen
In this paper, the identifying undmnaged-beam status based on singular spectrumanalysis (SSA) and wavelet neural networks (WNN) is presented